First international workshop on human endogenous retroviruses and diseases, HERVs & disease 2015. Issue 1 (December 2015) - Nath, Avindra; Küry, Patrick; Sciascia do Olival, Guilherme; Dolei, Antonina; Karlsson, Håkan; Groc, Laurent; Schneider, Marion; Kriesel, John; Touraine, Jean-Louis; Mallet, François; Marche, Patrice; Arnaud, Frederick; et al.
Abstract The First International Scientific Conference on Human Endogenous Retroviruses (HERVs) and Disease, Lyon-France, May 26-27th 2015, brought together scientific and medical specialists from around the world investigating the involvement of human endogenous retroviruses (HERVs) in complex human diseases.